Gender-Specific Duration of Parental Leave and Current Earnings - Benedikt Gerst; Christian Grund (Institute of Labor Economics (IZA), 2020)
Although male employees are increasingly making use of parental leave, gender differences in both usage and duration of parental leave are still prevalent. In this contribution, we explore the role of gender for the relation between the incidence/duration of parental leave and earnings after returning to a job. We use data on middle managers in the German chemical industry and show that parental leave pay gaps are much more severe for males than they are for females.
Keywords: M52; M12; J16; J31; 330; compensation; gender; parental leave; stigma; wages